OMPARATIVE STUDY OF ACADEMIC SUPERVISION, ACHIEVEMENT MOTIVATION AND TEACHER PERFORMANCE AT SOUTHEAST MALUKU REGENCY - Patrisius Rahabav; Sumarny Rumfot (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2020)
The purpose of this study was to test the significance of differences in academic supervision by principals on achievement motivation and teacher performance in elementary, junior high and senior high school / vocational high schools in Southeast Maluku Regency. The study population was 136 schools. Teacher samples were taken using a purposive sample technique based on criteria that had 10 years of teaching experience and were certified. The total sample of teachers was 160 people with the following details: elementary school: 52 teachers; Junior High School: 52 teachers; Senior High School: 52 teachers and Vocational High School: 4 teachers. In addition, 6 teachers and 3 principals became participants to be interviewed. Those interviewed did not include the number of samples. This research approach uses mixed methods. Data collection techniques used were questionnaires, interview guides and study documentation. Data analysis techniques used were descriptive statistics, ANOVA 1 lane and qualitative analysis. The results showed that there were no significant differences in the mean of academic supervision and teacher achievement motivation in the three sample groups and there were significant differences in teacher performance in the three samples. Based on the results of the qualitative analysis it was found that academic supervision was carried out without a program, the frequency and intensity of academic supervision conducted by the principal was very less. Supervision of school principals without using standard instruments, and the absence of the results of the analysis of supervision implementation Supervisors still use the bureaucratic-autocratic approach and are not participatory. Teacher achievement motivation is still very dominant triggered by welfare factors. The teacher has shown discipline, not delayed work. However, teachers have not displayed creative, innovative attitudes, independence in work, adaptability and have not reached high performance standards. The results of qualitative analysis of teacher performance variables, it was found that most teachers do not prepare their own lesson plans but copy and paste lesson plans from network sources or other colleagues; teacher copy paste Basic Competencies and indicators exactly as contained in the Minister of National Education Regulation. The teacher does not understand the preparation of HOTS (Higher Order Thinking Skill) questions and also has not been able to compile an assessment rubric. The lesson plans prepared by the teacher are only prerequisites for teaching; so it is only to fulfill formal-administrative demands and not be seen in class performance